2008
DOI: 10.2172/936761
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characterization of Chromate Contamination in the 100 Area Vadose Zone at the Hanford Site

Abstract: The major objectives of this study were to 1) determine the leaching characteristics of hexavalent chromium [Cr(VI)] from contaminated sediments collected from 100 Area spill sites; 2) elucidate possible Cr(VI) mineral and/or chemical associations that may be responsible for Cr(VI) retention in the Hanford Site 100 Areas through the use of macroscopic leaching studies, and microscale characterization of contaminated sediments; and 3) provide information to construct a conceptual model of Cr(VI) geochemistry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Microscopic characterization indicated that Cr was found on grain coatings but some Cr was associated with individual "hot-spots" and in altered minerals. Dresel et al (2008) recently published a report on the EM-funded work.…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations
“…Microscopic characterization indicated that Cr was found on grain coatings but some Cr was associated with individual "hot-spots" and in altered minerals. Dresel et al (2008) recently published a report on the EM-funded work.…”
Section: 3mentioning
confidence: 99%
“…The pH of these solutions, buffering capacity, and counter-ion concentration is critical to Na 2 Cr 2 O 7 solution vadose zone geochemistry. While the exact acidity of Hanford Site Cr stock solutions is not known, a 10% Na 2 Cr 2 O 7 (0.82 mol L -1 Cr) has a pH of 3.5, and a 70% Na 2 Cr 2 O 7 (8.96 mol L -1 Cr) may be lower (~1.5 to 2) (Dresel et al 2008). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, drawbacks to delivering amendments to heterogeneous porous media, with or without surfactants, include difficulty in containing amendments to the treatment zone and the potential for desorbed or surfactant-dissolved contaminants migrating to groundwater (Hanson et al 1993;Dresel et al 2008). Because preferential flow paths of the solution in the vadose zone may result, the amendment solution often bypasses the less permeable zones.…”
Section: Introductionmentioning
confidence: 99%